Fuzzy Expected Value Approach to Solve Integrated Supplier Selection and Inventory Control Problem in Fuzzy Environment - Sutrisno Sutrisno; Widowati Widowati; R. Heru Tjahjana (International Journal of Supply Chain Management, 2018)
In a production and inventory planning management, the future parameters like future demand, future product buying cost, future transport cost and future holding cost are obviously unknown/uncertain. To determine the optimal strategy in uncertain condition, a method that can handle the uncertainty of parameters is needed. If the historical data of the uncertain parameters are known then they can be approached by using probability distribution, but if there is no historical data then it cannot be used. In this paper, we propose a new mathematical optimization model with fuzzy parameters to solve an integrated supplier selection problem and inventory control problem in fuzzy environment where fuzzy variables are used to approach the uncertain parameters. To solve the corresponding optimization problem, we use fuzzy expected value based integer quadratic programming where the fuzzy variables are approximated by fuzzy expected value. From the numerical experiment results, the optimal strategy i.e. the optimal supplier and the optimal stored product volume were obtained and the actual inventory level followed the desired level with minimal total expected cost.